Distributed synchronization in large-scale wireless sensor networks using group consensus protocol - Yanliang Jin; Xiaoshuai Zhang; Bin Yao (International Journal of Distributed Sensor Networks, 2017)
This article analyzes the clock model of sensor nodes and the basic principle of time synchronization. Then, it systematically introduces the existing time synchronization mechanisms and compares their advantages and disadvantages. In order to solve the problems of consensus-based time synchronization, such as propagation delay and convergence speed, Group Consensus Time Synchronization algorithm is proposed. In this protocol, minimum data exchange is achieved for both frequency and phase offset compensation, and at the same time, the propagation delay is considered and compensated for. The simulation results show that the protocol can adapt to dynamic topology and be suitable to large-scale wireless sensor networks.